Affective Images Post-apartheid Documentary Perspectives - Kesting, Marietta (SUNY Press Open Access, 2017)
Affective Images examines both canonical and lesser-known photographs and films that address the struggle against apartheid and the new struggles that came into being in post-apartheid times. Marietta Kesting argues for a way of embodied seeing and complements this with feminist and queer film studies, history of photography, media theory, and cultural studies. Featuring in-depth discussions of photographs, films, and other visual documents, Kesting then situates them in broader historical contexts, such as cultural history and the history of black subjectivity and revolves the images around the intersection of race and gender. In its interdisciplinary approach, this book explores the recurrence of affective images of the past in a different way, including flashbacks, trauma, "white noise," and the return of the repressed. It draws its materials from photographers, filmmakers, and artists such as Ernest Cole, Simphiwe Nkwali, Terry Kurgan, Thenjiwe Niki Nkosi, Adze Ugah, and the Center for Historical Reenactments.